Inactivity and Its Associated Factors in Adults Scheduled for Noncardiac Surgery: The PAMP Phase I Study. Issue 2 (4th November 2016) - Cortés, Olga L.; Moreno, Karen; Alvarado, Paula; Povea, Camilo; Lloyd, Monique; Dennis, Rodolfo
Abstract: Purpose: The aim of this study was to determine the prevalence of physical inactivity and its associated factors in adult patients admitted to hospital for noncardiac surgery. Design: Cross‐sectional study. Methods: Five hundred able‐bodied patients (age ≥45 years) admitted to hospital, also participants in the VISION study, were recruited before noncardiac surgery. The physical activity level (PAL) was assessed with the International Physical of Activity Questionnaire. Logistic regression analysis was conducted to determine the associations between a number of predetermined factors and physical inactivity. Findings: Overall, 59.8% were inactive. Factors associated with inactivity included age, assistance with activities of daily living, and insulin‐dependent diabetes. Conclusion: A substantial number of patients scheduled for noncardiac surgery are inactive. Elderly patients, those needing assistance and those with long‐lasting diabetes may benefit from PAL assessment before surgery. Clinical Relevance: Healthcare providers should identify PALs and monitor for known risk factors to prepare patients for surgical procedures.